Kynurenic Acid and Its Synthetic Derivatives Protect Against Sepsis-Associated Neutrophil Activation and Brain Mitochondrial Dysfunction in Rats - Poles, Marietta Z.; Nászai, Anna; Gulácsi, Levente; Czakó, Bálint L.; Gál, Krisztián G.; Glenz, Romy J.; Dookhun, Dishana; Rutai, Attila; Tallósy, Szabolcs P.; Szabó, Andrea; Lőrinczi, Bálint; Szatmári, István; et al. (Frontiers in Immunology, 2021)
Background and aims: The systemic host response in sepsis is frequently accompanied by central nervous system (CNS) dysfunction. Evidence suggests that excessive formation of neutrophil extracellular traps (NETs) can increase the permeability of the blood–brain barrier (BBB) and that the evolving mitochondrial damage may contribute to the pathogenesis of sepsis-associated encephalopathy. Kynurenic acid (KYNA), a metabolite of tryptophan catabolism, exerts pleiotropic cell-protective effects under pro-inflammatory conditions. Our aim was to investigate whether exogenous KYNA or its synthetic analogues SZR-72 and SZR-104 affect BBB permeability secondary to NET formation and influence cerebral mitochondrial disturbances in a clinically relevant rodent model of intraabdominal sepsis. Methods: Sprague–Dawley rats were subjected to fecal peritonitis (0.6 g kg-1 ip) or a sham operation. Septic animals were treated with saline or KYNA, SZR-72 or SZR-104 (160 µmol kg-1 each ip) 16h and 22h after induction. Invasive monitoring was performed on anesthetized animals to evaluate respiratory, cardiovascular, renal, hepatic and metabolic parameters to calculate rat organ failure assessment (ROFA) scores. NET components (citrullinated histone H3 (CitH3); myeloperoxidase (MPO)) and the NET inducer IL-1β, as well as IL-6 and a brain injury marker (S100β) were detected from plasma samples. After 24h, leukocyte infiltration (tissue MPO) and mitochondrial complex I- and II-linked (CI–CII) oxidative phosphorylation (OXPHOS) were evaluated. In a separate series, Evans Blue extravasation and the edema index were used to assess BBB permeability in the same regions. Results: Sepsis was characterized by significantly elevated ROFA scores, while the increased BBB permeability and plasma S100B levels demonstrated brain damage. Plasma levels of CitH3, MPO and IL-1β were elevated in sepsis but were ameliorated by KYNA and its synthetic analogues. The sepsis-induced deterioration in tissue CI–CII-linked OXPHOS and BBB parameters as well as the increase in tissue MPO content were positively affected by KYNA/KYNA analogues. Conclusion: This study is the first to report that KYNA and KYNA analogues are potential neuroprotective agents in experimental sepsis. The proposed mechanistic steps involve reduced peripheral NET formation, lowered BBB permeability changes and alleviation of mitochondrial dysfunction in the CNS.